Impact of group practices on patients, physicians and healthcare systems: protocol for a scoping review. Issue 9 (21st September 2018) - Zwiep, Terry M; Greenberg, Joshua A; Balaa, Fady; McIsaac, Daniel I; Musselman, Reilly P; Raiche, Isabelle; Williams, Lara; Moloo, Husein
Abstract : Introduction: Group practices have potential benefits for patients, physicians and healthcare systems. Although group practices have been around for many years, research in this area is lacking and generally is centred around the economic benefits that may be realised from group practice. The aim of this scoping review is to identify the impact that group practices have on patients, physicians and healthcare systems to guide further research in this area. Methods and analysis: A scoping review will be performed based on the methodology proposed by Arksey and O'Malley and refined by Levac and colleagues. MEDLINE, EMBASE, Cochrane Central and Cochrane Economic Database will be searched from inception to present day to identify relevant studies that assess the impact of group practices on patient care, satisfaction and outcomes; physician quality of life, satisfaction and income and healthcare systems. Titles and abstracts will be screened by two members and the abstraction results charted and verified. Qualitative and quantitative analyses will be performed to identify key themes. Ethics and dissemination: Research ethics board approval is not required for this scoping review. A consultation phase will be used to discuss the results with key stakeholders followed by dissemination at local and national levels. We will also publish the results in a peer-reviewed journal.